KETAHANAN PANGAN INDONESIA: ANTARA JARGON DAN REALITAS - Hariadi, Untoro; Putri Perdana (Fakultas Pertanian Universitas Janabadra, 2025)
Food security has long been a political discourse in Indonesia, often presented through statistical claims of production surplus and reduced import dependency. However, empirical realities at the household level demonstrate persistent challenges related to equitable distribution, nutritional adequacy, environmental degradation, and farmer welfare. Through a qualitative literature review approach, this article critically examines government reports, academic publications, and field-based findings to deconstruct the multidimensional aspects of food security in Indonesia. The findings indicate that food security is frequently narrowed to rice production, overlooking local food diversity and systemic vulnerabilities exacerbated by climate change, land conversion, and the aging farmer population. Moreover, heavy reliance on imported commodities exposes the nation to global market fluctuations. True food security should transcend production-centric approaches and integrate fair access, nutritional adequacy, ecological sustainability, and smallholder farmer empowerment. This article emphasizes the need for a paradigm shift in food policy towards inclusive, resilient, and locally rooted food systems.